Characterization of a Nitric Oxide Synthase from the Plant Kingdom: NO Generation from the Green Alga Ostreococcus tauri Is Light Irradiance and Growth Phase Dependent - Foresi, Noelia Pamela (2010)
The search for a nitric oxide synthase (NOS) sequence in the plant kingdom yielded two sequences from the recently published genomes of two green algae species of the Ostreococcus genus, O. tauri and O. lucimarinus. In this study, we characterized the sequence, protein structure, phylogeny, biochemistry, and expression of NOS from O. tauri. The amino acid sequence of O. tauri NOS was found to be 45% similar to that of human NOS. Folding assignment methods showed that O. tauri NOS can fold as the human endothelial NOS isoform. Phylogenetic analysis revealed that O. tauri NOS clusters together with putative NOS sequences of a Synechoccocus sp strain and Physarum polycephalum. This cluster appears as an outgroup of NOS representatives from metazoa. Purified recombinant O. tauri NOS has a Km for the substrate L-Arg of 12 ± 5 μM. Escherichia coli cells expressing recombinant O. tauri NOS have increased levels of NO and cell viability. O. tauri cultures in the exponential growth phase produce 3-fold more NOS-dependent NO than do those in the stationary phase. In O. tauri, NO production increases in high intensity light irradiation and upon addition of L-Arg, suggesting a link between NOS activity and microalgal physiology.